Prostate size, nocturia and the digital rectal examination: a cohort study of 30 500 men. (23rd August 2016) - Stone, Benjamin V.; Shoag, Jonathan; Halpern, Joshua A.; Mittal, Sameer; Lewicki, Patrick; Golombos, David M.; Bedretdinova, Dina; Chughtai, Bilal; Barbieri, Christopher E.; Lee, Richard K.
Abstract : Objectives: To evaluate the utility of the digital rectal examination (DRE) in estimating prostate size and the association of DRE with nocturia in a population‐based cohort. Subjects and Methods: We identified all men randomized to the screening arm of the Prostate, Lung, Colorectal, and Ovarian Cancer Screening (PLCO) trial for whom DRE results were available. Men were excluded if they had a history of prostate surgery or incident prostate cancer. Prostate posterior surface area was derived from DRE sagittal and transverse estimates. Relationships between prostate posterior surface area, transrectal ultrasonography (TRUS), prostate‐specific antigen (PSA) and nocturia were analysed using intraclass correlation coefficients (ICCs), Spearman's rank correlation and multivariable logistic regression. Results: A total of 30 500 men met the inclusion criteria, with 103 275 screening visits containing paired DRE and PSA data. Digital rectal examination posterior surface area estimates had an ICC of 0.547 (95% CI 0.541–0.554) and were significantly yet modestly correlated with elevated PSA level ( r s = 0.18, P < 0.001) and TRUS prostate volume ( r s = 0.32, P < 0.001). Prostate posterior surface area was significantly associated with nocturia on multivariable analysis, but was not significant in stratified analysis of men with cardiovascular risk factors (hypertension, diabetes, high body mass index, stroke). In men without these risk factors, the highest quintile of DRE posterior surface area had 22% greater odds of nocturia than the lowest quintile (odds ratio 1.216, 95% CI 1.036–1.427). Conclusions: Digital rectal examination is a modestly accurate tool for measuring prostate volume. While DRE posterior surface area represents a statistically significant predictor of nocturia, the magnitude of effect suggests it has limited clinical utility for assessing this condition, particularly in the presence of cardiovascular risk factors.